Neuropathic pain in diabetic peripheral neuropathy and chronic low back pain syndrome: prevalence and characteristics - Zoran Vukojević; Aleksandra Dominović Kovačević; Sanja Grgić; Daliborka Tadić; Srdjan Mavija (Биомедицинска истраживања, 2025)
Introduction: Neuropathic pain (NP) is presented with a variety of symptoms, including "positive" (e.g., spontaneous pain, paresthesia, dysesthesia, allodynia, hyperalgesia, tingling, burning) and "negative" (e.g., numbness and loss of sensa tion) features. The most common causes are diabetic peripheral neuropathy (DPN) and chronic low back pain syndrome (CLBPS). This study aimed to determine the frequency and characteristics of NP in these conditions and to evaluate the sensitivity of commonly used diagnostic questionnaires. Methods: We examined 80 patients with DPN (40 with and 40 without NP) and 80 patients with CLBPS (40 with and 40 without NP). Assessments included electromyography (EMG), NIS-LL scoring for DPN, MRI of the lumbosacral spine for CLBPS and three NP questionnaires: Pain Detect Questionnaire (PDQ), Leeds Assessment of Neuropathic Symptoms and Signs (LANSS), and Douleur Neuropathique 4 (DN4). Results: In DPN, NP was associated with greater disease severity (higher NIS-LL scores), with allodynia being the most dis tinguishing symptom. In CLBPS, key NP characteristics varied across the three questionnaires. Tingling was common in both conditions, regardless of NP status. Conclusion: Allodynia is the defining feature of NP in DPN. NP questionnaires demonstrated lower diagnostic accuracy for NP in CLBPS compared to DPN. DN4 demonstrated the highest sensitivity for NP detection.
Keywords: peripheral neuropathic pain; diabetic peripheral neuropathy; chronic low back pain syndrome